A comprehensive overview of framework for developing sustainable energy internet: From things-based energy network to services-based management system. (October 2021) - Wu, Ying; Wu, Yanpeng; Guerrero, Josep M.; Vasquez, Juan C.
Abstract: Energy Internet (EI) envisions a future energy system with sustainable concerns of efficiency, economy and environment by achieving flexibility of multi-energy-integrated physical space, digitalization of data-driven cyber space and interaction of customer-aware social space. To systemically understand how EI manages energy, data and information flows, a comprehensive investigation from multi-angle perspectives is presented in this paper. The core building blocks are categorized into three-layered framework: energy-oriented network, communication-oriented network and service-oriented management. Furthermore, this paper provides a multi-disciplinary portrait of today's EI in terms of architecture, technologies, standards, services and platforms. Finally, open issues, future trends and challenges for development of sustainable EI are discussed. Highlights: Investigation of Energy Internet from the energy-oriented, communication-oriented and service-oriented perspectives. Concepts, infrastructures and key technologies are reviewed and discussed in the energy-oriented network. Architectures, protocols and key technologies are reviewed and discussed in communication-oriented network. Services and platforms are reviewed and discussed in service-oriented management network. Challenges and future trends for sustainable Energy Internet are discussed from cyber, physical and social space aspects.